2023
DOI: 10.1007/s44197-023-00089-1
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Positional Obstructive Sleep Apnoea in a Sample of the Saudi Population

Abstract: Purpose Positional obstructive sleep apnoea (POSA) is of important clinical significance, as positional treatment can augment or obviate continuous positive airway pressure. This study aimed to determine the prevalence of POSA and its characteristics using different definitions. Methods We retrospectively examined a cohort of patients who underwent polysomnography (PSG) between 2013 and 2019 at two sleep centres. Demographic data and PSG data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Additionally, acid reflux may stimulate the vagus nerve, inhibiting the medullary respiratory center and preventing proper contraction of the respiratory muscles ( 41 ), which may also lead to apnea. From a sleep position perspective, the supine position not only facilitates airway obstruction due to tongue and throat tissue collapse ( 42 ) but also increases the likelihood of gastroesophageal reflux ( 43 ), which can exacerbate respiratory issues by causing breathing pauses and snoring. A study on the relationship between renalase and OSA found that more severe OSA patients often have more shallow sleep ( 44 ), which may also help explain why GERD can simultaneously lead to OSA, insomnia, and subjectively shortened sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, acid reflux may stimulate the vagus nerve, inhibiting the medullary respiratory center and preventing proper contraction of the respiratory muscles ( 41 ), which may also lead to apnea. From a sleep position perspective, the supine position not only facilitates airway obstruction due to tongue and throat tissue collapse ( 42 ) but also increases the likelihood of gastroesophageal reflux ( 43 ), which can exacerbate respiratory issues by causing breathing pauses and snoring. A study on the relationship between renalase and OSA found that more severe OSA patients often have more shallow sleep ( 44 ), which may also help explain why GERD can simultaneously lead to OSA, insomnia, and subjectively shortened sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Using the definitions of POSA and e-POSA previously defined by Cartwright [ 12 ] and Mador et al [ 15 ], respectively, POSA and e-POSA were found to have a prevalence of 60.1% and 26.1% in our study population. Other studies across many countries using the similar definitions also reported the prevalence of POSA and e-POSA to range from 53% to 62.3% and from 20.1% to 33.8%, respectively [ 2 , 9 , 12 , 13 , 21 , 22 ]. In a study by Sabil et al in a French population of OSA patients (n=6437), the prevalence of POSA and e-POSA were reported to be 53.5% and 20.1%, respectively, and both were independently associated with time in supine position, male sex, younger age, lower AHI, and lower BMI [ 12 ].…”
Section: Discussionmentioning
confidence: 86%
“…Different definitions of positional sleep apnea have been developed in regards to the severity of OSA, as defined by the apnea-hypopnea index (AHI) in supine and non-supine positions [ 2 , 11 ]. Accordingly, 3 distinct clinical types of OSA have been defined, namely POSA, exclusive POSA (e-POSA), and non-positional OSA (non-POSA) [ 2 , 9 , 12 , 13 ]. POSA is OSA with at least double frequency of breathing abnormalities during supine than during the lateral position, OSA occurring exclusively in the supine position (normalized AHI in non-supine positions) is defined as e-POSA, and non-POSA is defined as a high frequency of breathing abnormalities in all positions [ 2 , 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations